The Realistic Acting Method as a Mechanism of Attenuation of the Actor’s Presence in Theatre and Cinema - Mauro (Universidad de Buenos Aires (UBA) – Buenos Aires, Argentina), Karina (Revista Brasileira de Estudos da Presença, 2022)
We have analyzed the realistic acting methodology as a mechanism of attenuation of the actor’s presence. We consider that Stanislavski’s system constituted the first technical resolution to an old aspiration for the transparency of the scene toward the referent. For that, the realistic acting method proposes the reduction of the disruptive nature of the public exhibition of the actor’s body and action through a series of procedures that will be analyzed in this paper.